Uji Aktivitas Antioksidan dan Fenolik Total Fraksi Etil Asetat Daun Sembung (Blumea balsamifera (L.) DC) - Azimatur Rahmi; Tika Afriani; Linda Hevira; Wike Widiawati (Universitas Andalas, 2021)
The aim of this study is to investigate antioxidant activity and total phenolic content of ethyl acetate fraction of Sembung leaves. SembungÂ (Blumea balsamifera L.) is a plant that has the potential as an antioxidant because it contains secondary metabolites of alkaloids, steroids, flavonoids, saponins, and phenolic compounds. In this study, antioxidant activity was tested by using 1,1-diphenyl-2-picrylhydrazyl (DPPH) for free radical scavenging activity assay. Evaluation of total phenolic content was tested by using the Folin-Ciocalteau method. The results showed that the ethyl acetate fraction of Sembung leaves possess showed medium antioxidant activity with IC50 valueof 221.821 compare with reference standard ascorbic acid with IC50 value 68.25 ppm. The ethyl acetate fraction of Sembung leaves has a total phenolic content of 161.101 mg GAE/g. This study provided that Blumea balsamifera leaves possess antioxidant.